2011
DOI: 10.1016/j.pep.2011.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Expression and purification of myristoylated matrix protein of Mason-Pfizer monkey virus for NMR and MS measurements

Abstract: Matrix proteins play multiple roles both in early and late stages of the viral replication cycle. Their N-terminal myristoylation is important for interaction with the host cell membrane during virus budding. We used Escherichia coli, carrying N-myristoyltransferase gene, for the expression of the myristoylated His-tagged matrix protein of Mason-Pfizer monkey virus. An efficient, single-step purification procedure eliminating all contaminating proteins including, importantly, the non-myristoylated matrix prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…Protein preparation was described previously when we demonstrated that the C-terminal extension of MA does not affect its structure. 23 To determine the structure of myrMA, we used high-resolution multidimensional NMR spectroscopy in combination with computational methods. Myristoylation caused large changes in the 1 H/ 15 N chemical shifts when compared to the spectra of the non-myristoylated analogue; therefore, we assigned all protein resonances de novo .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein preparation was described previously when we demonstrated that the C-terminal extension of MA does not affect its structure. 23 To determine the structure of myrMA, we used high-resolution multidimensional NMR spectroscopy in combination with computational methods. Myristoylation caused large changes in the 1 H/ 15 N chemical shifts when compared to the spectra of the non-myristoylated analogue; therefore, we assigned all protein resonances de novo .…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that the PPHis segment does not influence the structure of the (myr-)MA. 23 The N-terminus of the myrMA is fixed by the myristoyl group so that the first helix is located closer to the rest of the protein. Additionally, the orientation of the second helix is slightly different between the two forms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myristoylated M‐PMV matrix protein was prepared as previously described . Briefly, the gene for matrix protein, as well as eukaryotic N ‐myristoyltransferase, was inserted into E. coli DH5α strain.…”
Section: Methodsmentioning
confidence: 99%
“…Pr78 is modified by an N-terminal myristic acid residue that is mostly buried within the folded protein [4]. Following interaction of Gag with the plasma membrane the exposure of this myristic acid moiety appears to be critical for envelopment and budding of the virus [5].…”
Section: Introductionmentioning
confidence: 99%